A Case of Kawasaki Disease Complicated With Cerebral Salt-Wasting Syndrome - Oshima, Masanari; Fukuhara, Junji; Noto, Takanori; Noguchi, Teppei; Murabayashi, Masao; Ayusawa, Mamoru; Morioka, Ichiro (Frontiers in Pediatrics, 2020)
We report the case of a 3-year-old boy who developed severe hyponatremia and unconsciousness during an episode of Kawasaki disease (KD). He was diagnosed with cerebral salt wasting syndrome (CSWS), which has not previously been reported as a complication of KD. He was diagnosed with Kawasaki disease with fever and four clinical signs and received intravenous immunoglobulin (IVIG) on the day after onset. Hyponatremia had been observed and it worsened after IVIG. At first, syndrome of inappropriate antidiuretic hormone secretion (SIADH) was suspected, but his hyponatremia did not improve by restriction of water intake. The patient’s consciousness level decreased along with the worsening hyponatremia. Electroencephalography revealed abnormal electrical discharge concordant with acute encephalopathy. Laboratory data showed hypouricemia with high FEUA (fractional excretion of uric acid), in addition to a negative balance of both Na and water. We diagnosed Kawasaki disease complicated with CSWS. The patient improved promptly with appropriate Na supplementation and water correction.